Pengaruh Brisk Walking Exercise terhadap Penurunan Tekanan Darah: Systematic Review - Rizky Rachmatullah; Widyatuti Widyatuti; Sukihananto Sukihananto (Faletehan Health Journal, 2022)
Brisk walking exercise is an intervention that can lower blood pressure in hypertensive patients. It is very effective to stimulate muscle contraction, increase heart rate and oxygen in the tissues and break down glycogen. This exercise can reduce the process of plaque formation through increased glucose and fat utilization. The research objective was to determine the effectiveness of brisk walking exercise on lowering blood pressure of hypertensive patients. This study was a systematic review. The articles were obtained from online database, namely Science Direct, Scopus, Wiley Online, Oxford Journal, Research Gate, and Google Scholar from 2010 to 2020. The search obtained 10 articles which showed that brisk walking exercise had a significant effect on lowering blood pressure in hypertensive patients. Brisk walking exercise should be developed as a clinical intervention of lowering blood pressure in health services such as hospitals and public health centers.